EFFECTS OF BLACK SOLDIER FLY CARCASS FLOUR ON FEED AGAINST DIGESTIBILITY, LIVER AND BLOOD IMAGE OF SANGKURIANG CATFISH (CLARIAS GARIEPINUS) - Huda, Muhammad Aidil; Sunarno, Mas Tri Djoko; Nurhudah, Moch (Aquacultura Indonesiana, 2020)
The purpose of this study was to determine the effect of Black Soldier fly carcass flour on feed on digestibility, liver and blood features in Sangkuriang catfish (Clarias gariepinus).  Sangkuriang catfish (Clarias gariepinus) used measuring 9-12 cm with a weight of ± 5.27 g. The aquariums are used as many as 5 pieces measuring 100 cm x 50 cm x 51 cm. The amountof sangkuriang catfish (Clarias gariepinus) stocked in the aquarium is 10 per aquarium and fed 6% of the total weight of all test fish. The results showed that the digestibility value of 50% black soldier fly carcass flour (CF)  treatment gave the best results. In addition, the liver picture in the 50% CF treatment did not show any abnormalities in the liver of the Sangkuriang catfish (Clarias gariepinus). Amount of blood cells in 50% CF treatment is in optimal condition. Based on these results indicate that the administration of Black Soldier fly carcass flour at CF 50% treatment gives the best results on digestibility, liver picture and blood of Sangkuriang catfish (Clarias gariepinus), so that Black Soldier fly carcass flour can be used in feed formula